Observation of Photonic Topological Floquet Time Crystals. Issue 5 (4th February 2022) - Wang, Bing; Quan, Jiaqi; Han, Jianfei; Shen, Xiaopeng; Wu, Hongwei; Pan, Yiming
Abstract : The two main research questions on time crystals are: What is a time crystal? Is there a material that is spontaneously crystalline in time? This study synthesizes a photonic material of topological Floquet time crystals and experimentally observes its indicative period‐ 2 T 2T beating. A single‐particle picture is explicitly reconstructed of discrete time‐crystalline phase and is revealed using an appropriately‐designed photonic Floquet simulator the rigid period‐doubling as a signature of the breakage of the discrete time‐translational symmetry. Unlike the requirement of the many‐body localization, the photonic Floquet time crystal is derived from a newly defined single‐particle topological phase that can be extensively accessed by many pertinent nonequilibrium and periodically‐driven platforms. The observation will drive theoretical and technological interests toward condensed matter physics and topological photonics. Abstract : A first photonic material is reported of single‐particle topological Floquet time crystals in waveguide‐array simulation and its topologically protected period‐doubling behavior is observed. The construction and observation of topological Floquet time crystals may drive both theoretical and technological interests toward photonics, quantum simulation platforms, and condensed matter physics, and may also demystify time crystals for the public.